Physics Research Aided Worksheet Based RGV To SMA With Setting Guided Discovery Learning - Aisatul Haidaria; I Ketut Mahardika; Alex Harijanto (Pancaran Pendidikan, 2017)
This research is the study of physics (Newton's laws) aided worksheet based on RGV to SMA with guided discovery learning setting. This study aims to determine the guided discovery learning model aided worksheet based on RGV on Newton's laws in senior high school. The study in this article uses a descriptive method by describing the result of examined data qualitatively in the form of critical reviews written by experts from a variety of sources. Sources of information are obtained from data observation, journals, documentation, interviews, proceedings or books of reference and then the data are analysed as a process of data clarifying and grouping. The results showed that the guided discovery learning model aided worksheets based on RGV on Newton's law material in senior high school can make learning activity be more effective because the students can gain learning experience directly so that they can understand the learning concept easily, which means that it can improve their learning achievement and their science process skills.